Gerakan Sosial Kewirausahaan Berbasis Komunitas Desa Oleh Ibeka - Swasti, Cantika; Sutriyono, (Asketik: Jurnal Agama dan Perubahan Sosial, 2021)
Electricity energy in the future, because it is realized that fossil energy will sooner or later be depleted and will be eliminated by humans, besides that its reserves are depleting and the impact of carbon emissions resulting from combustion systems produced by motorized vehicles and industry has become a central issue for the global community. In fact, the government is also encouraging the creation of renewable energy and launching the acceleration of electric vehicles. So that electricity can be said as energy that will be consumed by mankind in the future, leaving energy that has a negative impact on the environment and health. Thus, the community's efforts to create cheap and affordable electrical energy for the community, villages need support and appreciation from both the government and entrepreneurs, as has been done by IBEKA. Institute of Business and People's Economics (IBEKA). This IBEKA has a mission to develop renewable energy which is beneficial for community independence in the socio-economic and environmental aspects. His research aims to analyze the entrepreneurial process based on rural communities, considering that most of Indonesia's population resides in rural areas. The potential of rural areas is enormous to be developed well economically, culturally, socially and politically. The theoretical approach used to analyze the process of social entrepreneurship is based on the Business Canvas Model (CMB). This study uses a qualitative descriptive methodology. The result of this research is that IBEKA has succeeded in developing a hybrid social enterprise model that combines social and business.